Nanostructures and their applications - Ramrakhiani, Meera (Recent Research in Science and Technology, 2012)
Nanostructures have been described as ‘novel materials whose size of elemental structure has been engineered at the nanometer scale’. Materials in the nanometer size range commonly exhibit fundamentally new behavior. Moreover, intervention in the properties of materials at the nanoscale enables the creation of materials and devices with enhanced or completely new characteristics and functionalities. Understanding the science of nanomaterials is important and curiosity driven not only because of the fascinating nature of the subject but also for overwhelming and novel applications of nanoscale systems in almost all branches of technology.Nanotechnology can be understood as a technology of design, fabrication and application of nanostructures and nanomaterials.The field of nanoscience and nanotechnology is interdisciplinary in nature and it is being perused by physicists, chemists, materials scientists, biologists, engineers, computer scientists etc. Nanomaterials may be classified on the basis of dimensionality and modulation. Some special nanostructures like nanotubes, nanoporous materials, aerogels, zeolites, core-shell structures have also come up with their novel characteristics. A number of methods have been used for the synthesis of nanostructure with various degrees of success and many direct and indirect techniques are employed for their characterization. The fact, which makes the nanostructures interesting, is that the properties become size dependent in nanometer range because of surface effect and quantum confinement effect. The geometric structure, chemical bonds, ionization potential, electronic properties, optical properties, mechanical strength, thermal properties, magnetic properties etc. are all affected by particle sizes in nanometer range. Nanomaterials exhibit properties often superior to those of conventional coarse-grained materials. These include increased strength/hardness, enhanced diffusivity, improved ductility/toughness, reduced density, reduced elastic modulus, higher electrical resistivity, increased specific heat, higher thermal expansion coefficient, lower thermal conductivity, increased oscillator strength, blue shifted absorption, increased luminescence and superior soft magnetic properties in comparison to conventional bulk materials. All of these properties are being extensively investigated to explore possible applications. The fascinating field of nanotechnology has wide range of applications. Use of nanostructutred materials has produced transistors with record low speed and lasers with low threshold current. These are being used in compact disk player systems, low noise amplification in satellite receivers as sources for fiber optic communication etc. Constructive applications of nanomaterials include self-cleaning glass, UV resistant wood coating etc. Nanoscale devices are being used in medical field also for diagnosis, treatment and prevention of diseases and in drug delivery system, magnetic resonance imaging, radioactive tracers etc. Importance of nanotechnology is growing day by day. Many more applications may be possible with the novel and peculiar properties of nanostructures.